GESTUR SISWA SMP BERDASARKAN TAHAPAN BERPIKIR VAN HIELE - Mustafa A.H Ruhama; Hasan Hamid; Ardiana Ardiana (EDUKASI, 2026)
The aim of the research is to describe the pointing gestures, representational gestures and writing gestures of students of SMP Negeri 1 Kota Ternate based on  Van Hiele's level of thinking. This research uses a case study. The subjects of this research are 2 students of SMP Negeri 1 Kota Ternate and 2 students have gone through the subject selection stage. The researcher was the main instrument and recording tool, the VHGT question sheet and interview guide as supporting instruments. The data collection procedure was carried out by recording students while completing the VHGT, interviews and recording the details of students' answers using a handycam/android phone. Qualitative data analysis was carried out exploratively and continuously until complete or no new data was obtained about students' gestures based on Van Hiele's level of thinking. Students used pointing gestures at Van Hiele's level of thinking 0, 1 and 2 to focus attention on certain visual objects or geometric shapes, focus attention on objects related to the properties of the shapes, and focus attention on objects related to the properties of geometric shapes and connect them with the properties of other geometric shapes. Students used representational gestures at Van Hiele's level of thinking 0, 1 and 2 to describe or visualize geometric shapes concretely, describe or simulate the properties or rules that fulfill geometric shapes, and describe or simulate the properties or rules that fulfill geometric shapes. Students use their respective writing gestures at Van Hiele's level of thinking 0, 1 and 2 based on the visual characteristics or appearance of geometric shapes, when writing relationships in a geometric shape and to understand the relationship between one geometric shape and another.